Preparation method of wide-temperature-range fast-charging type iron-based sulfate positive electrode material and sodium ion battery
Through liquid-solid synthesizing technology, sodium sulfate and ferrous sulfate are uniformly dispersed, and high-speed ball milling is carried out with conductive carbon materials to prepare nano-size active particles and high-efficiency conductive network composite materials, solving the problem of poor long cycle stability of sodium ion battery positive electrode materials at high magnifications, and achieving fast charging and discharge in a wide temperature domain and high magnification long cycle stability.
Patent Information
- Application Number
- CN202411582849.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-04-25
AI Technical Summary
The existing sodium ion battery positive electrode materials have poor long cycle stability at high magnifications and insufficient electronic conductivity. Due to the limitations of solid-phase ball milling method, uniform mixing of elements is difficult to achieve, resulting in impurities generation and stress increase, affecting the cycle stability of the battery.
The liquid-solid synthesizing strategy is adopted to uniformly disperse sodium sulfate and ferrous sulfate in deionized water, combine vacuum drying and high-speed ball milling technology to uniformly mix conductive carbon materials, and finally calcined at low temperature in a protective atmosphere, nano-sized active particles and composite materials with high-efficiency conductive networks are prepared.
It achieves fast charging and discharge and high-magnification long cycle stability in a wide temperature range of -25~60℃, with high purity, reduced impurities, and improved conductivity, and is suitable for large-scale energy storage.
Smart Images

Figure CN119890416A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a wide-temperature-range fast-charging sulfate positive electrode material and a sodium ion battery, belonging to the technical field of sodium ion batteries. Background Art
[0002] In order to solve the pain points of intermittent and variable layout environment of clean renewable resources such as wind energy and solar energy, it is imperative to vigorously develop new energy storage technologies with fast charging, wide temperature range and long life. Globally, lithium-ion batteries dominate new energy storage technologies. However, due to the limited reserves of lithium resources and their concentrated regional distribution, the price of lithium-ion batteries has fluctuated in recent years due to factors such as upstream and downstream supply and demand and regional political turmoil. Sodium-ion batteries are considered to be another potential candidate for large-scale energy storage and industrial and commercial energy storage due to their low cost, abundant sodium reserves, and excellent high and low temperature performance. At present, the research on negative electrode materials for sodium-ion batteries is mainly focused on the development of low-cost, high-performance hard carbon negative electrodes, while the research on positive electrode materials for sodium-ion batteries is mainly committed to developing new materials suitable for the next generation of new energy storage technologies in the routes of polyanionic compounds, organics, layered metal oxides, Prussian blue and the like. Prussian blue materials still have a long way to go to achieve long cycle life due to the problem of crystal water defects in the lattice. Transition metal oxides have poor safety and lifespan, making them difficult to use in large-scale energy storage. Polyanionic compounds exhibit excellent high-temperature performance, low-temperature performance, and long-cycle stability due to their stable three-dimensional frameworks, but these materials have low specific capacity at high-rate charge and discharge due to their poor electronic conductivity.
[0003] Iron-based polyanionic sulfate sodium 2+2δ Fe 2-δ (SO4)3 positive electrode material can be prepared by solid-phase ball milling combined with low-temperature sintering technology. It has an operating voltage of up to 3.8V and can achieve a mass energy density of >380Wh / kg, but its poor electronic conductivity leads to insufficient high-rate discharge capacity and poor long-cycle stability. In addition, since the solid-phase ball milling method cannot achieve uniform mixing of Na, Fe, S and O elements at the molecular level, it is difficult to diffuse the element concentration during the low-temperature sintering process, and impurities such as Fe3O4 or Na6Fe(SO4)4 are easily generated. The multi-phase coexistence hybrid system will eventually undergo repeated charge and discharge at high rates, and the active Na 2+2δ Fe 2-δ The difference in expansion rate between (SO4)3 particles and impurity particles can easily generate stress, which eventually leads to significant capacity decay during long cycles at high rates. Sulfate-type Na with greatly improved electronic conductivity can also be obtained by adding conductive materials to an aqueous solution containing sodium sulfate and ferrous sulfate for ultrasonic dispersion, preparing dry powder and then sintering at low temperature. 2+2δFe 2-δ (SO4)3 composite positive electrode material. Due to the uniform mixing of Na, Fe, S and O elements at the molecular level, the impurity content of Fe3O4 and Na6Fe(SO4)4 can be minimized under reasonable proportion control, and it is expected to prepare pure phase Na 2.6 Fe 1.7 (SO4)3 and composite positive electrode materials. It cannot be ignored that conductive carbon materials are generally hydrophobic, and simple ultrasonic dispersion is difficult to make them completely and evenly dispersed in aqueous solution. Therefore, the prepared composite positive electrode material particles are prone to uneven distribution of particle conductivity, which is specifically manifested in the high-rate repeated charge and discharge process. The Na 2+2δ Fe 2-δ The (SO4)3 particles are unable to fully utilize their capacity at high rates and eventually become inactivated, resulting in insufficient discharge capacity at high rates and a significant attenuation of the long-cycle capacity retention rate. Summary of the invention
[0004] Based on this, the present invention provides a preparation method of a wide-temperature fast-charging iron-based sulfate positive electrode material and a sodium ion battery. The preparation method belongs to a liquid-solid collaborative synthesis strategy, which takes into account the advantages of both the solid-phase method and the liquid-phase method. It can not only achieve uniform mixing of Na, Fe, S and O elements at the molecular level, effectively ensuring the high purity of the product and the uniformity of element distribution, but also achieve uniform mixing of the precursor and the conductive carbon material in a short time to obtain a composite material with nano-sized active particles and uniformly wrapped high-efficiency conductive network. The finally prepared iron-based sulfate positive electrode material can achieve fast charging and discharging and high-rate long-cycle stability in a wide temperature range of -25 to 60°C, and has the prospect of being applied to the field of large-scale energy storage.
[0005] Furthermore, the wide temperature range fast-charging iron-based sulfate cathode material of the present invention can be prepared by the following technical scheme:
[0006] Sodium sulfate and ferrous sulfate are added to deionized water according to a certain Na / Fe molar ratio, and an appropriate amount of antioxidant is added to prevent Fe 2+ Hydrolyzed to Fe 3+ , and then rapidly stirred to obtain a light green aqueous solution with uniformly dispersed solute. The aqueous solution is vacuum dried to obtain a precursor powder, which is then evenly mixed with the conductive carbon material by high-speed ball milling, and finally the ball-milled powder is calcined in a tubular furnace with a protective atmosphere to obtain the wide temperature range fast-charging iron-based sulfate cathode material.
[0007] Furthermore, the Na / Fe molar ratio is at least one of 2.2:1.9, 2.4:1.8, 2.6:1.7 and 2.8:1.6.
[0008] Furthermore, the antioxidant comprises at least one of ascorbic acid, citric acid or high-purity iron wire.
[0009] Furthermore, the vacuum drying temperature is 150-200° C., and the drying time is 12-24 hours.
[0010] Furthermore, the conductive carbon material comprises at least one of carbon nanotubes, graphene, and conductive carbon black (SP, acetylene black, Ketjen black), and the addition amount is 1-10wt.%
[0011] Furthermore, the ball milling speed is 600-1000 rpm, and the ball milling time is 6-12 hours.
[0012] Furthermore, the protective atmosphere contains at least one of Ar, N2, and He.
[0013] Furthermore, the calcination temperature is 350-450° C., and the calcination time is 12-24 hours.
[0014] Beneficial Effects
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] First, the preparation of Na 2.6 Fe 1.7 The phase in the (SO4)3@CNTs cathode material is pure Na 2.6 Fe 1.7 (SO4)3, no impurities such as Fe3O4 and Na6Fe(SO4)4 that are easily caused by element segregation were detected.
[0017] Second, the conductive carbon material is evenly wrapped around the nanoscale active particles, forming a coherent conductive network between the particles, fully ensuring the electrochemical performance of each active particle. At the same time, the nanoscale active particles can shorten the diffusion distance of sodium ions and effectively improve the diffusion kinetics of sodium ions.
[0018] Third, the preparation of Na 2.6 Fe 1.7 (SO4)3@CNTs positive electrode material can achieve rapid charging and discharging and stable high-rate long cycling in a wide temperature range of -25 to 60°C.
[0019] In general, the Na prepared by the present invention 2.6 Fe 1.7 (SO4)3@CNTs positive electrode material has high purity and can be charged and discharged at high rates. More importantly, it can be used stably in a wide temperature range and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.
[0021] Figure 1 It is prepared Na 2.6 Fe 1.7 XRD pattern of (SO4)3@CNTs positive electrode material.
[0022] Figure 2 It is prepared Na 2.6 Fe 1.7 SEM image of (SO4)3@CNTs positive electrode material.
[0023] Figure 3 is Na in Example 1 2.6 Fe 1.7 Rate discharge performance of (SO4)3@CNTs positive electrode material at room temperature 25℃.
[0024] Figure 4 is Na in Example 1 2.6 Fe 1.7 1C cycle performance of (SO4)3@CNTs positive electrode material at room temperature 25℃.
[0025] Figure 5 is Na in Example 1 2.6 Fe 1.7 2C cycle performance diagram of (SO4)3@CNTs positive electrode material at high temperature of 60℃.
[0026] Figure 6 is Na in Example 1 2.6 Fe 1.7 1C cycle performance diagram of (SO4)3@CNTs positive electrode material at low temperature of -25℃. DETAILED DESCRIPTION
[0027] In order to better understand the technical solution of the present invention, further detailed description is given below in conjunction with specific embodiments and comparative examples.
[0028] Example 1
[0029] The preparation method of the wide temperature range fast-charging iron-based sulfate cathode material and the specific preparation process of the sodium ion battery of the present invention are as follows:
[0030] Preparation of positive electrode materials: Sodium sulfate and ferrous sulfate were added to deionized water at a Na / Fe molar ratio of 2.6:1.7, and an appropriate amount of ascorbic acid was added to prevent Fe 2+ Hydrolyzed to Fe 3+, and then quickly stirred to obtain a light green aqueous solution with uniformly dispersed solutes. The aqueous solution was vacuum dried at 170°C for 12 hours to obtain a precursor powder, which was then mixed with 5wt% of a highly conductive carbon material by high-speed ball milling. Finally, the ball-milled powder was calcined at 400°C for 12 hours in a tube furnace with a protective atmosphere to obtain Na 2.6 Fe 1.7 (SO4)3@CNTs positive electrode material.
[0031] Preparation of positive electrode: weigh Na and 2.6 Fe 1.7 (SO4)3@CNTs active material, conductive carbon black, PVDF binder, after adding appropriate amount of NMP, quickly stir evenly to form slurry, finally coat the slurry on aluminum foil, and obtain the positive electrode material pole piece of Example 1 after vacuum baking, rolling and cutting.
[0032] Negative electrode material sheet preparation: Use metal sodium sheet as negative electrode material sheet
[0033] Battery preparation: In a glove box filled with argon (moisture <0.1ppm, oxygen <0.1ppm), the obtained positive electrode sheet, negative electrode sheet and separator are respectively placed into button battery shells, and after injecting an appropriate amount of electrolyte, they are sealed to make sodium ion battery button half-cells or full cells.
[0034] Figure 1 The Na prepared in Example 1 2.6 Fe 1.7 The X-ray diffraction pattern of (SO4)3@CNTs material shows that Na 2.6 Fe 1.7 The (SO4)3@CNTs material has high crystallinity, and no diffraction peaks of impurities such as Fe3O4 and Na6Fe(SO4)4 were observed, indicating that the material is of high purity.
[0035] Figure 2 The Na prepared in Example 1 2.6 Fe1 .7 The SEM image of (SO4)3@CNTs material shows that the primary particles are relatively small, about 100-300nm. Uniformly wrapped carbon nanotubes are observed around the primary particles, and they are cross-linked and contacted with each other, forming a battery transmission channel between particles, which is conducive to the battery to exert high rate capacity and high capacity retention rate.
[0036] Figure 3 is the Na prepared in Example 1 2.6 Fe 1.7The rate discharge diagram of (SO4)3@CNTs positive electrode material shows that the material has excellent high-rate discharge capacity, showing a discharge specific capacity of about 56mAh / g and 34mAh / g at 50C and 100C, respectively.
[0037] Figure 4 is the Na prepared in Example 1 2.6 Fe 1.7 The 1C cycle performance diagram of (SO4)3@CNTs positive electrode material at room temperature 25°C shows that the first cycle discharge capacity is about 80mAh / g, and the capacity retention rate is about 96% after 100 cycles.
[0038] Figure 5 is the Na prepared in Example 1 2.6 Fe 1.7 1C cycle performance diagram of (SO4)3@CNTs positive electrode material at low temperature of -25℃. The capacity retention rate is about 100% after 100 cycles.
[0039] Figure 6 is the Na prepared in Example 1 2.6 Fe 1.7 2C cycle performance diagram of (SO4)3@CNTs positive electrode material at high temperature of 60°C. The capacity retention rate is about 93% after 100 cycles.
[0040] Example 2
[0041] The manufacturing method of the positive electrode sheet, the negative electrode sheet and the battery is the same as that of Example 1, except that the amount of CNTs added during the preparation of the positive electrode material is 2 wt.%.
[0042] Example 3
[0043] The manufacturing methods of the positive electrode sheet, the negative electrode sheet and the battery are the same as those in Example 1, except that the amount of CNTs added during the preparation of the positive electrode material is 10 wt.%.
[0044] Example 4
[0045] The method for preparing the positive electrode sheet, the negative electrode sheet and the battery is the same as that in Example 1, except that the molar ratio of Na / Fe used in the preparation of the positive electrode material is 2.2:1.9.
[0046] Example 5
[0047] The method for preparing the positive electrode sheet, the negative electrode sheet and the battery is the same as that in Example 1, except that the molar ratio of Na / Fe used in the preparation of the positive electrode material is 2.4:1.8.
[0048] Example 6
[0049] The method for making the positive electrode sheet, the negative electrode sheet and the battery is the same as that in Example 1, except that the molar ratio of Na / Fe used in the preparation of the positive electrode material is 2.8:1.6.
[0050] Comparative Example 1
[0051] The method for making the positive electrode sheet, the negative electrode sheet and the battery is the same as that in Example 1, except that CNTs are not added during the preparation of the positive electrode material.
[0052] Comparative Example 2
[0053] The manufacturing method of the positive electrode sheet, the negative electrode sheet and the battery is the same as that of Example 1, except that in the preparation process of the positive electrode material, sodium sulfate, ferrous sulfate and CNTs are directly ball-milled and mixed and then calcined to obtain the positive electrode material.
[0054] Comparative Example 3
[0055] The preparation method of the positive electrode sheet, the negative electrode sheet and the battery is the same as that in Example 1, except that in the preparation process of the positive electrode material, CNTs are directly added to a mixed aqueous solution of sodium sulfate and ferrous sulfate and then ultrasonically dispersed, and then vacuum dried and directly calcined to obtain the positive electrode material.
[0056] Test experiment
[0057] Room temperature charge and discharge performance test: At room temperature (25°C), a 1C charge and discharge cycle test was performed in the range of 2 to 4.5 V for all batteries prepared in Examples 1 to 6 and all Comparative Examples 1 to 3, and the first-cycle discharge specific capacity was recorded. The capacity retention rate after the 100th cycle was calculated based on the first-cycle discharge specific capacity.
[0058] High temperature charge and discharge performance test: For all batteries prepared in Examples 1 to 6 and all Comparative Examples 1 to 3, a 2C charge and discharge cycle test was performed at a temperature of 60°C in the range of 2 to 4.5V, and the first cycle discharge specific capacity was recorded. The capacity retention rate after the 100th cycle was calculated based on the first cycle discharge specific capacity.
[0059] Low-temperature charge and discharge performance test: For all batteries prepared in Examples 1 to 6 and all Comparative Examples 1 to 3, a 1C charge and discharge cycle test was performed at a temperature of -25°C and in the range of 2 to 4.5V. The first-cycle discharge specific capacity was recorded, and the capacity retention rate after the 100th cycle was calculated based on the first-cycle discharge specific capacity.
[0060] Fast charge and discharge performance test: The battery prepared in Example 1 was subjected to a 1C to 100C fast charge and discharge performance test in the range of 2 to 4.5V at room temperature (25°C), and the rate discharge specific capacity data was recorded.
[0061] Table 1 shows the battery performance test data of all recorded embodiments and comparative examples.
[0062]
[0063] Table 2 shows the room temperature rapid charge and discharge performance test data of Example 1.
[0064]
[0065] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a wide temperature range fast-charging sulfate positive electrode material and a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The positive electrode plate is made of pure phase Na 2.6 Fe 1.7 (SO4)3@CNTs active material, conductive carbon black, and PVDF binder are configured in a certain mass fraction; the negative electrode plate is a metallic sodium plate or is configured by hard carbon, conductive carbon black and PVDF binder in a certain mass fraction; the diaphragm is a glass fiber diaphragm, and the electrolyte is a carbonate electrolyte for sodium ion batteries.
2. The wide temperature range fast-charging sulfate cathode material according to claim 1, characterized in that: The pure phase Na 2.6 Fe 1.7 The (SO4)3@CNTs positive electrode material is a nanoscale primary particle with an average particle size of 100 to 300 nm. There is a continuous carbon nanotube conductive network around the nanoparticles, and the carbon nanotube addition amount is 1 to 10 wt.%.
3. The method for preparing a wide temperature range fast-charging sulfate cathode material according to claim 1, characterized in that: Sodium sulfate and ferrous sulfate are added to deionized water according to a certain Na / Fe molar ratio, and an appropriate amount of antioxidant is added to prevent Fe 2+ Hydrolyzed to Fe 3+ , and then rapidly stirred to obtain a light green aqueous solution with uniformly dispersed solute. The aqueous solution is vacuum dried to obtain a precursor powder, which is then evenly mixed with a highly conductive carbon material by high-speed ball milling, and finally the ball-milled powder is calcined in a tubular furnace with a protective atmosphere to obtain the wide temperature range fast-charging iron-based sulfate cathode material.
4. The method for preparing a wide temperature range fast-charging sulfate cathode material according to claim 3, characterized in that: The Na / Fe molar ratio is at least one of 2.2:1.9, 2.4:1.8, 2.6:1.7 and 2.8:1.
6.
5. The method for preparing a wide temperature range fast-charging sulfate cathode material according to claim 3, characterized in that: The antioxidant comprises at least one of ascorbic acid, citric acid or high-purity iron wire.
6. The method for preparing a wide temperature range fast-charging sulfate cathode material according to claim 3, characterized in that: The vacuum drying temperature is 150-200° C., and the drying time is 12-24 hours.
7. The method for preparing a wide temperature range fast-charging sulfate cathode material according to claim 3, characterized in that: The highly conductive carbon material comprises at least one of carbon nanotubes, graphene, and conductive carbon black (SP, acetylene black, Ketjen black), and the added amount is 1 to 10 wt.%.
8. The method for preparing a wide temperature range fast-charging sulfate cathode material according to claim 3, characterized in that: The ball milling speed is 600-1000 rpm, and the ball milling time is 6-12 hours.
9. The method for preparing a wide temperature range fast-charging sulfate cathode material according to claim 3, characterized in that: The protective calcination atmosphere comprises at least one of Ar, N2, and He.
10. The method for preparing a wide temperature range fast-charging sulfate cathode material according to claim 3, characterized in that: The calcination temperature is 350-450° C., and the calcination time is 12-24 hours.